Evaluation of the Antimicrobial Effect of Pre-Synthesized Novel Antibiotic Electrospun Nanofibers as an Intracanal Delivery Strategy for Regenerative Endodontics: A Randomized Clinical Trial - Elgamal, Sara Gamal; El-Shafei, Jealan M.; Azzazy, Hassan Mohamed El-Said; Dwedar, Reham Ali; El-Khodary, Sherif Adel (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The aim of this study is to evaluate the antimicrobial effect of pre-synthesized novel antibiotic loaded electrospun nanofibers and compare it with conventional triple antibiotic paste when used in patients with immature necrotic teeth. METHODS: Antibiotic loaded nanofibers were fabricated by electrospinning. Thirty-four patients with immature necrotic teeth were included in the study. In the first visit, access cavity preparation was performed to obtain the first bacteriological sample (S1). The canals were thoroughly irrigated using sodium hypochlorite 1.5% and a second sampling was performed (S2). Patients were randomly divided into two groups according to the intracanal medicament used: Modified triple antibiotic paste (MTAP) loaded electrospun nanofibers or MTAP paste. At the second appointment, the third samples (S3) were taken. The intracanal bacterial count was determined using the spread plate culture technique. Scanning electron microscopy (SEM) was used to examine the morphology of the fabricated MTAP loaded electrospun nanofibers. RESULTS: Both MTAP nanofibers and MTAP paste resulted in significant reduction of bacterial count after the irrigation step. MTAP nanofibers resulted in significantly higher percent reduction of bacterial count (p < 0.05). CONCLUSIONS: It was concluded that electrospinning technology can be used to fabricate antibiotic containing nanofibers which can results in enhanced disinfection in regenerative endodontic procedures.